Aktualisai Dan Dampak Hadhanah Pada Anak Yang Tidak Diasuh Oleh Salah Satu Orang Tua (Studi di Kapanewon Piyungan) - Khiyaroh, Khiyaroh (Jurnal El-Thawalib, 2025)
Hadhanah applied by parents who are still complete with parents who have disappeared or separated, there must be differences. A child who is cared for by a parent who is complete and both give each other attention will grow up better than one who is only cared for by one of the parents. This study examines how the concept of hadhanah applied by parents is incomplete to children, and how it affects children who grow up without the role of parents who are complete with the perspective of Islamic law and positive law. In reality, in the environment of children who grow up without the role of one of the fathers or mothers, there is a negative impact that arises on the child. This research is a field research conducted in Kapanewon Piyungan, Bantul Regency, DIY with a qualitative research type. The approach in this study is with a positive legal approach and Islamic law with the theory of sharia maqashid. The author took data by direct interviews with the source. Then the data from the interview results were analyzed with the approach of the Marriage Law and the theory of maqashid as-sharia. The results of the study are that not all single parents can maximize into two roles as a father and mother at the same time. This causes negative impacts on children, including psychological disorders, deviant behavior and lack of socialization. In the study of Islamic law, it is not in accordance with the principles of hifzh nasl and hifzh aql.